P–625 Does endogenous progesterone play a role in unexplained infertility? A systematic review. (6th August 2021) - Raperport, C; Chronopoulou, E; Homburg, R; Khan, K; Bhide, P
Abstract: Study question: Does endogenous progesterone play a role in unexplained infertility? A systematic review investigating the possibility of altered progesterone-mediated change leading to reduced endometrial receptivity in women with unexplained infertility. Summary answer: The evidence suggests that many of the measurable actions of endogenous progesterone are reduced in women with unexplained infertility when compared with controls. What is known already: Unexplained infertility is the diagnosis given to heterosexual couples who fail to conceive despite normal semen analysis, regular ovulation and patent tubes. The underlying pathology is likely to relate to embryonic failure to implant. Endometrial receptivity is largely mediated by luteal phase progesterone which controls many different molecular pathways involved in secretory transformation. It is possible that defective actions of progesterone could contribute to this condition. To date however, there is minimal published literature on the role of progesterone in unexplained infertility. We therefore felt it important to combine the results of all trials measuring progesterone-related outcomes in unexplained infertility. Study design, size, duration: A systematic review was performed using standard Cochrane methodology. We searched Medline, Embase and CINAHL databases from inception to December 2020 and additionally hand-searched. The study was prospectively registered on Prospero (CRD42020141041). The search strategy was designed to identify all types of primary research published in English that investigated women with unexplained infertility and reported outcomes that relate to progesterone. Newcastle Ottawa Scoring and NHLBI assessment of bias scoring was performed. Participants/materials, setting, methods: The study population was women with unexplained infertility. Included studies had no controls, fertile controls or controls with other diagnoses associated with subfertility. Outcomes were either upstream affecting progesterone production/release or receptor expression or downstream measuring results of progesterone-mediated processes. The results were summarised in a narrative review. Meta-analysis was not possible due to varying methodological heterogeneity. Main results and the role of chance: 36 studies were included. No difference was found in 18 studies in progesterone levels (serum, peritoneal and salivary) between women with unexplained infertility and control groups. Despite this, 32 of the 36 included studies demonstrated a significant difference between progesterone-mediated outcomes in the unexplained infertile and control groups. 5 ultrasound studies all reported increased resistance and decreased flow on doppler studies of uterine, ovarian and spiral arteries and reduced endometrial and sub-endometrial perfusion. No significant difference was found in luteal phase endometrial thickness in 2 studies. Endometrial dating was reported by 11 studies. 8/11 studies reported significantly higher numbers (20–38%) of 'out-of-phase' endometrium in women with unexplained infertility compared with controls. Endometrial biopsy results measuring different cell adhesion molecules, monoclonal antibodies and other molecules involved in endometrial transformation as well as expression of responsible genes and steroid hormone receptors were included. All the progesterone-mediated outcome measures listed above were reduced in unexplained infertile women except β3 integrin which reported contradictory results and SGK1 expression which was reported in 1 study. This trend towards support for the hypothesis may be more important than any individual finding. The quality of the included studies was variable and hence the strength of the recommendations moderate. Limitations, reasons for caution: The number of studies measuring each outcome was limited. The study quality varied from good to poor. Methodological heterogeneity between studies prevented meta-analysis. The strength of the study however comes from the originality of the research, the variety of included outcomes and that 32/36 papers reported results supporting the hypothesis. Wider implications of the findings: The findings of this systematic review support the need for larger, well designed research on this topic. If altered progesterone-mediated receptivity is implicated in unexplained infertility, it may be possible to offer other therapeutic interventions to improve outcomes as an alternative or adjunct to standard fertility treatment. Trial registration number: NA